ChemInform Abstract: Enantioselective Phospha‐Michael Addition of Diarylphosphines to β, γ‐Unsaturated α‐Ketoesters and Amides. Issue 1 (January 2015) - Chew, Renta Jonathan; Teo, Kai Yuan; Huang, Yinhua; Li, Bin‐Bin; Li, Yongxin; Pullarkat, Sumod A.; Leung, Pak‐Hing
Abstract The first protocol involving the catalytic enantioselective phospha‐Michael addition of β, γ‐unsaturated α‐ketoesters and amides is presented.